2016
DOI: 10.1080/03075079.2016.1196353
|View full text |Cite
|
Sign up to set email alerts
|

Her majesty the student: marketised higher education and the narcissistic (dis)satisfactions of the student-consumer

Abstract: Intensifying marketisation across higher education (HE) in England continues to generate critical commentary on the potentially devastating consequences of market logic for learning. In this paper, we consider the student-consumer prominent in these debates as a contested yet under-analysed entity. In contrast to the dominance of homo economicus discursively constructed in policy, we offer a psychoanalytically-informed interpretation of undergraduate student narratives, in an educational culture in which the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
151
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(173 citation statements)
references
References 58 publications
2
151
0
1
Order By: Relevance
“…Consistent with these views, our findings provide insights into extant academics' perceptions of the impact of the consumerist shift on a range of HEI stakeholders. Consistent with reports from other studies (Naidoo and Jamieson 2005;Nixon et al 2016), the majority of academics within our study note that student attitudes have changed, with academics perceiving their students to simply expect or want a degree in exchange for their fees. This reported perception is consistent with the notion of purchasing a degree as a product, as opposed to being engaged as the co-creators of a knowledge generation service.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with these views, our findings provide insights into extant academics' perceptions of the impact of the consumerist shift on a range of HEI stakeholders. Consistent with reports from other studies (Naidoo and Jamieson 2005;Nixon et al 2016), the majority of academics within our study note that student attitudes have changed, with academics perceiving their students to simply expect or want a degree in exchange for their fees. This reported perception is consistent with the notion of purchasing a degree as a product, as opposed to being engaged as the co-creators of a knowledge generation service.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, research has shown there has been an increase in evidence suggesting that consumer-based practices, notions and perceptions are permeating into UK higher education institutions (HEIs) (Nixon et al 2016;Woodall et al 2014). Many of these developments have occurred since the introduction of tuition fees, following which UK HEI leaders have implemented strategies, policies and procedures which focus on income and revenue maximisation (Natale and Doran 2012), as opposed to the traditional staple learning and teaching experiences (Marginson 2012;Nixon et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It provides an overarching means to communicate with students about a central purpose of these activities, how they may relate to each other and to course learning outcomes. With sceptical studentconsumers, a strong educational rationale which speaks to students' future use is necessary (Nixon et al 2016). It may also persuade educators that devoting time to work-intensive activities such as using exemplars, co-creating rubrics, and undertaking self and peer assessment and feedback is worthwhile.…”
Section: Discussionmentioning
confidence: 99%